2011
DOI: 10.1097/mcg.0b013e318210ff17
|View full text |Cite
|
Sign up to set email alerts
|

Liver Failure After Transarterial Chemoembolization for Patients With Hepatocellular Carcinoma and Ascites

Abstract: Preexisting ascites increases the mortality in patients with HCC receiving TACE. In patients with HCC and ascites, Child-Turcotte-Pugh class B and gastrointestinal bleeding are associated with liver failure after TACE. Post-TACE liver failure is a common event and predicts a decreased survival in patients with HCC and ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 29 publications
3
33
1
Order By: Relevance
“…According to previous reports, TACE has been proved to significantly improve the survival rate in HCC patients . Whereas, accumulating evidence has demonstrated that TACE may lead to the irreversible deterioration of liver function as evaluated by the elevation of serum aminotransferases and the decrease of serum albumin (ALB), occasionally resulting in hepatic failure . Toxicity of chemotherapeutics drugs used in TACE has been suggested as the main cause of treat‐related complication .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous reports, TACE has been proved to significantly improve the survival rate in HCC patients . Whereas, accumulating evidence has demonstrated that TACE may lead to the irreversible deterioration of liver function as evaluated by the elevation of serum aminotransferases and the decrease of serum albumin (ALB), occasionally resulting in hepatic failure . Toxicity of chemotherapeutics drugs used in TACE has been suggested as the main cause of treat‐related complication .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Whereas, accumulating evidence has demonstrated that TACE may lead to the irreversible deterioration of liver function as evaluated by the elevation of serum aminotransferases and the decrease of serum albumin (ALB), occasionally resulting in hepatic failure. [8][9][10] Toxicity of chemotherapeutics drugs used in TACE has been suggested as the main cause of treat-related complication. 11,12 Owing to selective uptake of the mixture of antineoplastic drugs and iodized oil by tumorous tissue, the side effects of TACE on peritumoral liver tissue are unlikely to be attributed by drug toxicity alone.…”
Section: Introductionmentioning
confidence: 99%
“…Hence there was no heterogeneity in terms of primary treatment due to the inclusion of patients with decompensated cirrhosis. The TACE was not recommended for patients with HCC and ascites due to a more vulnerable chance of the ischemic injury after TACE (31). However, the ascites variable was only one of the parameters that would have in uence on the survival.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Hsin et al demonstrated that patients with post-TACE hepatic failure had a 2.13-fold increased risk of mortality, a majority of whom died within 12 months of TACE. 13 Likewise, if a HCC patient develops acute hepatic toxicity after SBRT and dies of liver failure within 12 months, it possibly may be due to negative effects of the preceding SBRT.…”
Section: Introductionmentioning
confidence: 99%